Characterization and role of derived dissolved organic matter on arsenic mobilization in alluvial aquifers of Punjab, Pakistan. (July 2020) - Malik, Aroosa; Parvaiz, Ambreen; Mushtaq, Nisbah; Hussain, Ishtiaque; Javed, Tariq; Rehman, Hafiz Ur; Farooqi, Abida
Abstract: Biogeochemical mobilization of arsenic in groundwater depends on the presence of dissolved organic matter (DOM) that likely promotes the As release, i.e., reductive dissolution, complexation, competition, and electron shuttling. We investigated the role of DOM in As release, along with its complete characterization, in the Indus plain of Pakistan, one of the worst arsenic impacted zones in the South Asian region. In total, 60 groundwater and 15 soil samples, collected at six sites from north to south within the flood plain of the Ravi River, Lahore, Pakistan were investigated. Arsenic concentration ranged from 9.61 μg/L to 386 μg/L in the groundwater samples (high As observed in areas close to the river). Dissolved organic carbon (DOC) in 29 groundwater samples ranged between 0 and 10.1 mg-C/L. A moderately positive correlation of As with DOC and Fe in the northern part of the study area suggest the reductive dissolution of FeOOH associated with dissolved organic matter (DOM). The reductive dissolution plays an essential role for As enrichment in the area evidenced by the lower concentrations of SO4 2−, NO3 −, and PO3 4− and a non-correlative pattern with As. In contrast, a positive correlation of As with PO3 4−, DOC, and HCO3 − in the southern part indicate competitive desorption behind the As release. Fluorescence excitation-emission matrix intensity data of DOM indicate the maximum presence of humic-like substances in the northern part that gradually shifts to aromatic, fulvic and protein type towards the southern part. Specific ultraviolet absorbance and fluorescence index display aromatic and terrestrial (allochthonous) sources of DOM near the riverbank and mixed (both allochthonous and autochthonous) source away from the river. The positive correlations of As with DOC and fluorescence intensity also attest that DOM played a vital role in the As mobilization in groundwater of the study area. Graphical abstract: Image 1 Highlights: As concentartions were above the WHO limit with an increasing trend from northern to southern side of the study area. Reductive dissolution, competitive desorption with dissolved organic matter probabaly results in As mobilization in groundwater. Geochemical data show terrestrially-derived dissolved organic matter in northern part while exhibit mixed source in the southern part.